Investigating urban growth boundary as mechanism to plan for sustainable urban development - Samat, Narimah; Mahamud, Mohd Amirul; Maghsoodi, Javad M; Abu Bakar, Azmeer; Tan, Mun Leong; Hj. Mohd. Noor, Norzailawati (Malaysian Institute of Planners, 2021)
Urban encroachment into the peri-urban areas has blurred the borders between urban and rural areas. Thus, the urban growth boundary (UGB) has been used to encourage the sustainable development of cities and improve long-term planning efficiency. Studying the understanding of the UGB concept in ensuring sustainable development in Malaysia would be beneficial. This study aimed to investigate the perception and understanding of the UGB concept and function to achieve sustainable urban development. An online survey was conducted involving 82 experts, which comprised planners from PLANMalaysia and academicians in the field of urban planning. Results indicated that the perception of the UGB score was significantly greater by 1.16 than the normal score of 3, which indicated that the experts agreed that UGB could improve the urban development. The findings also indicated that the existing planning policy and inclusion of UGB had protected agricultural and natural land; however, stricter and tighter borderless development should be conducted.